Website Penerimaan Mahasiswa Baru (Studi Kasus : STT Pagar Alam) - Desi Puspita (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2016)
The purpose of this research is to design and build the website of new student acceptance (PMB) Sekolah Tinggi Teknologi Pagar Alam (STTP). Management and processing of new student admissions data (PMB) is still done manually therefore there is need of availability of support website at Sekolah Tinggi Teknologi Pagar Alam (STTP). With this officers in the process of processing new student admissions data to be more effective, both in terms of time, place, cost, and energy using PHP programming language and MySQL database. The system development methodology used is Web Enginering namely Customer Communication, Planning, Modeling, Construction, Deployment. With this website is expected to overcome the current problems this research is done to create a new admissions website (PMB) is done online with terms connected to the Internet network.